Position of women in company Lagardere Travel Retail - Šimůnková, Lucie; Křečková Kroupová, Zuzana, 1972-; Volfová, Jitka, 1982-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The thesis is studying the position of women in business, specifically in Lagardère Travel Retail in the Czech Republic. In the theoretical part, I will focus on the situation of women in the world in business but I will also mention fields like politics which have an influence on the business environment of the country. The practical part assesses the situation in Lagardère Travel Retail. It will describe the hierarchy of the company and presence of female workers in different levels of the management.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses